Active ageing: mature women perceptions about fashion (ModaPalavra e-periódico, 2016)
Thiswork researchis an exploratory apliedon thetheme of old age andaims to understandmore about such universe. Theinformation foundis usedas a subsidy fora reflection onthe apparel of women over 70sliving inTrês Coroas/RS.The ageing population andits causes,the reality of theBrazilianold people,the physical andpsychological changes that affectmature individuals and foreshortening of the “new old age” are some of the issuescovered in this article. Also presented are the field research results appliedin the formoffocus groupsas a way tocollectthe necessaryinformationaboutthe chosen target audience.
Keywords: aging; behavior; fashion